Enzymatic Regioselection for the Synthesis and Biodegradation of Porphysome Nanovesicles - Lovell, Jonathan F.; Jin, Cheng S.; Huynh, Elizabeth; MacDonald, Thomas D.; Cao, Weiguo; Zheng, Gang (Angewandte Chemie International Edition, 2012)
A select few: An enzyme screen is used to identify two enzymes that selectively cleave porphyrin–lipid regioisomers (see picture). Either of the isomerically pure conjugates assembles into physically similar porphysome nanovesicles. Although porphysomes formed from both regioisomers are stable in serum in vivo, only one regioisomer rapidly degrades upon uptake in the liver.